(untitled) (Bangladesh Journal of Medical Science, 2017)
Thyroglossal duct carcinoma (TGDC) is a rare disease with many reported cases. The recurrence in such cases after surgical removal may be seen after cyst excision. Sistrunks operation is recommended, as it has a very low recurrence rate. The case which present as recurrence demonstrate histological pattern similar to a thyroglossal duct cyst. We present a case of recurrence of thyroglossal cyst, with a solid internal component on ultrasonography (USG). On histopathology the solid internal component proved to be papillary carcinoma. To our knowledge, our paper is the first case of recurrent thyroglossal cyst with a papillary carcinoma preoperatively suspected on USG Bangladesh Journal of Medical Science Vol.16(1) 2017 p.166-169